Differential Activity of Antioxidants in Testicular Tissues Following Administration of Chlorophytum borivilianum in Gamma-Irradiated Swiss Albino Mice - Vyas, Ruchi; Kesari, Kavindra Kumar; Slama, Petr; Roychoudhury, Shubhadeep; Sisodia, Rashmi (Frontiers in Pharmacology, 2022)
Irradiation induced oxidative stress causes variable expression of antioxidant enzymes in a tissue specific manner. Testicular tissues carry complex process of spermatogenesis, previous studies indicated that post-irradiation testicular damages require long-term recovery before complete resumption. This study estimated differential expression of antioxidant enzymes following administration of Chlorophytum borivilianum root extract (CRB) in response to irradiation induced oxidative stress. Activity of various important endogenous enzymatic defence system were evaluated and correlated for strength of association. Results indicated significant increase in level of glutathione (GSH) and activity of GSH related antioxidant enzymes in irradiated mice treated with CRE and CRE-AgNPs (silver nanoparticles biosynthesized using Chlorophytum borivilianum root extract) in comparison with not pre-treated with CRE or CRE-AgNPs. Reciprocal elevation was observed in related enzymes i.e. Glutathione S-Transferase activity (GST), Glutathione Peroxidase (GR), and Glutathione Peroxidase Activity (GPx). Elevation in activity of Catalase (CAT) and Superoxide Dismutase (SOD) was also evident in both irradiated groups pre-treated with CRE-AgNPs. However, expression of CAT in CRE treated irradiated group was similar to that of the non-treated irradiated group. Higher association between CAT-SOD, CAT-GPx, and GR-GST was observed. Overall, it was observed that testicular cells post-irradiation in all groups go through intense oxidative stress, however, groups pre-treated with CRE or CRE-AgNPs indicated better toleration and resumption of antioxidant capacity. CRE or CRE-AgNPs pre-treated non-irradiated groups mostly remained within control range indicating stimulated expression of antioxidants.